Photochemical green synthesis of calcium-alginate-stabilized Ag and Au nanoparticles and their catalytic application to 4-nitrophenol reduction - Saha, Sandip (Langmuir : the ACS journal of surfaces and colloids, 2010)
Silver and gold nanoparticles have been grown on calcium alginate gel beads using a green photochemical approach. The gel served as both a reductant and a stabilizer. The nanoparticles were characterized using UV-visible spectroscopy, X-ray diffraction (XRD), scanning and transmission electron microscopy (SEM and TEM), energy dispersive X-ray (EDS), and selected area electron diffraction (SAED) analyses. The particles are spherical, crystalline, and the size ranges for both Ag and Au nanoparticles are <10 nm. It is noticed from the sorption experiment that the loading of gold on calcium alginate beads is much more compared to that of Ag. The effectiveness of the as-prepared dried alginate-stabilized Ag and Au nanoparticles as a solid phase heterogeneous catalyst has been evaluated, for the first time, on the well-known 4-nitrophenol (4-NP) reduction to 4-aminophenol (4-AP) in the presence of excess borohydride. The reduction was very efficient and followed zero-order kinetics for both Ag and Au nanocomposites. The effects of borohydride, initial 4-NP concentration, and catalyst dose were evaluated. The catalyst efficiency was examined on the basis of turnover frequency (TOF) and recyclability. The catalytic efficiency of alginate-based Ag catalyst was much more compared to that of the Au catalyst. The as-prepared new solid-phase biopolymer-based catalysts are very efficient, stable, easy to prepare, eco-friendly, and cost-effective, and they have the potential for industrial applications